PENDIDIKAN ISLAM MODERAT DALAM BINGKAI KEARIFAN LOKAL - Mohammad Muchlis Solichin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Moderatism in Islam teaches balance, inclusivism, tolerance, and love of peace. With this value, Muslims appear with a peaceful face and tolerance against various differences. Pesantren al-Amin Prenduan, the value of modernism instilled these values, in the process of learning, in the subject of al-Qur, an, Al-Hadith, Fight and Islamic History. While outside the learning process, the planting of moderate values ​is done in extra-curricular activities, santri life management, and incidental activities in pesantren. This paper intends to examine 1) the implementation of moderate education in Al-Amin Islamic Boarding School in the framework of local wisdom Madurese, 2) constructivism learning model in cultivating the values ​​of moderatism, and 3) learning strategies used in moderatism education. The research method used is qualitative research, by using observation, interview, and documentation. The results of this research are 1) The planting of moderatism in Pesantren al-Amin is conducted through 1) the learning process based on the curriculum that is applied (intrakurikuler). 2) learning outside of the curriculum (extra curricular), and 3) hidden curriculum (hidden curricular). As a boarding school located in Madura, this pesantren conducts its education process in the framework of the local wisdom of Madura that is respect to the teacher.